The Impact of SQ3R on Reading Comprehension in High School Students - Gurung , Sunita (Journal of NELTA, 2025)
Despite the fact that reading comprehension is crucial for academic success not much research has been done on the best teaching methods for Nepali high school students especially in private schools where resources and learning environments may differ from those in public ones. This action research fulfills this gap by investigating the impact of the Collaborative SQ3R strategy on the reading comprehension skills of Grade 9 and 10 students in a private secondary school in Kathmandu. Employing a quasi-experimental one-group pretest-posttest design, the research measured comprehension gains quantitatively and explored student perceptions qualitatively. Results reveal a substantial improvement in reading comprehension among students who engaged in the Collaborative SQ3R method compared to those receiving traditional instruction. After a thorough analysis, the research supports the widespread adoption of the Collaborative SQ3R strategy as a valuable pedagogical tool for improving literacy outcomes and better preparing Nepalese students for academic and real-world challenges.